Successful Treatment of Pneumocephalus Using a Free-Style Chimeric Free Flap From a Scarred Thigh. Issue 7 (October 2018) - Visconti, Giuseppe; Pagliara, Domenico; Bianchi, Alessandro; La Rocca, Giuseppe; Olivi, Alessandro; Salgarello, Marzia
Abstract : Abstract: Pneumocephalus is an air collection in cranial cavity caused by accidental exposition of intracranial compartment after trauma or surgery. Skull base reconstruction with free flap is a useful surgical tool to avoid cerebral herniation or intracranial infection. The authors describe a patient of pneumocephalus following anterior skull base meningioma resection, unsuccessfully treated with 2 attempts of fascia lata grafts harvested from both thighs. A free-style chimeric anterolateral thigh free flap was performed using middle third of rectus femoris muscle to fill the planum spheno-ethmoidalis defect and adipocutaneous paddle for postoperative monitoring and for favoring a tension free skin closure. Free-style dissection with limited undermining in the previously scarred thigh was performed to avoid donor-site complication. Postoperative course was uneventful with complete resolution of the pneumocephalus.